Cognitive Impairment in Neurodegenerative Movement Disorders - Abdelnour, Carla; Poston, Kathleen L. (Seminars in Neurology, 2023)
Patients with neurodegenerative movement disorders can develop cognitive impairment during the disease. Cognitive symptoms have been associated with decreased quality of life, higher caregiver burden, and earlier institutionalization, and are therefore critical for physicians to understand and address. The evaluation of cognitive performance of patients with neurodegenerative movement disorders is important for providing adequate diagnosis, management, prognosis, and support patients and their caregivers. In this review, we discuss the features of the cognitive impairment profile of commonly encountered movement disorders: Parkinson's disease, dementia with Lewy bodies, multiple system atrophy, progressive supranuclear palsy, corticobasal syndrome, and Huntington's disease. In addition, we provide neurologists with practical guidance and evaluation tools for the assessment and management of these challenging patients.
Keywords: neurodegenerative movement disorders; cognitive impairment; neuropsychiatric symptoms; dementia